Public health implications of Sabarimala mass gathering in India: A multi-dimensional analysis. Issue 37 (September 2020) - Rajasekharan Nayar, Kesavan; Fazaludeen Koya, Shaffi; Mohandas, K.; Sivasankaran Nair, Sabari; Chitra, Grace A; Abraham, Minu; Lordson, Jinbert
Abstract: Introduction: Mass gathering for religious and spiritual purposes are common in India. However, mass gathering health and travel medicine is still in its infancy in India. Objectives: The study explored bio-medical, environmental and psycho-social dimensions of mass gathering in Sabarimala pilgrimage, which is annually attended by 25 million pilgrims. Methods: In a cross sectional design, the investigators travelled the pilgrim trail and stayed in the shrine area to conduct the interviews (sample = 1259), to observe the practices as well as to assess the environmental conditions including sanitation. We did in-depth interviews of a subset of samples of the pilgrims, laboratory tests for water quality and secondary analysis of health services data. Result: 43.4% pilgrims reported at least one health problem. Leg pain, joint/muscle pain, breathlessness, were the common symptoms. Pilgrims expressed concern about drinking water and food safety and majority of them felt the crowd management as unsatisfactory. Untreated sewage and solid waste were found to pollute the water downstream. Average patient presentation rate for 2014–2017 was 4999.6 per 100, 000 pilgrims and referral to Hospital Rate was 19 per 100, 000 pilgrims. Mortality rate ranged from 18.5 to 21 per 100, 000 pilgrims among those who attended the health centers for ailments. Death due to Coronary Artery Heart Disease (CAHD) has slightly decreased over the period of 3 years from 97.6% to 85.1%. Conclusion: Data with respect to safety, health and environment at the pilgrim sites need to be continuously assessed to understand changes and trends and to develop an effective mass gathering and safe pilgrimage policy (MGSPP).